Characterization and Direct Modulation of a Multi-Section PIC Suited for Short Reach Optical Communication Systems - Mohab N. Hammad; Aleksandra Kaszubowska-Anandarajah; M. Deseada Gutierrez Pascual; Pascal Landais; Prajwal D. Lakshmijayasimha; Gaurav Jain; Prince M. Anandarajah (Photonics, 2020)
A multi-section active photonic integrated circuit (PIC) is characterized in detail to gauge its suitability as a transmitter for short reach applications. The PIC is 1.5 mm long and consists of two lasers integrated in a master-slave configuration, which enables optical injection locking (OIL) of the slave laser. The beneficial impact of the injection is characterized by static and dynamic measurements. The results show a reduction of the optical linewidth from 8 MHz to 2 MHz, a relative intensity noise (RIN) value as low as −154.3 dB/Hz and a 45% improvement of the slave laser modulation bandwidth from 9.5 GHz to 14 GHz. This frequency response enhancement allows the direct modulation of the slave gain section at a data rate of 10.7 Gb/s and an error-free transmission over 25 km of standard single-mode fiber (SSMF). Transmission performance of the injected case shows a 2 dB improvement in the minimum optical power required to achieve a bit error rate of <semantics>3.8×10−3</semantics> (hard decision forward error correction limit). These results demonstrate that the multi-section PIC can serve as an attractive cost-efficient transmitter in a wide variety of low-cost short-reach data communication applications.